Anesthesia-Related Mortality in Children: A Surgeon’s Perspective - Chukwubuike Kevin Emeka (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Background: Anesthesia-related mortality refers to death resulting from the complications of anesthesia or death due to at least one anesthesia-related complication happening as a cause among the multiple causes of death. The aim of this study was to evaluate the incidence and causes of anesthesia-related mortality in pediatric patients, as experienced by a surgeon.  Materials and Methods: This was a retrospective study of children aged 15 years and younger who died at the pediatric surgery unit of Enugu State University Teaching Hospital (ESUTH) Enugu, Nigeria following administration of anesthesia between January 2010 and December 2019. Results: A total of 31,210 pediatric anesthesias/surgeries were performed during the study period; out of which 78 mortalities occurred due to anesthesia. There was male predominance and the median age of the patients was 4 years with a range of 1 week to 12 years. Mortality occurred more in neonates and during emergency surgeries. Airway complications and intussusception were the most common etiology of mortality and pathology in the children respectively. About two-thirds of the deaths occurred in the operating room before commencement of the surgery. Conclusion: Anesthesia-related deaths in children in middle income country like Nigeria are higher than what is obtainable in developed countries. The risk factors for anesthesia-related mortality include male gender, neonates and emergency surgeries. Airway problem is a common cause of mortality.